2015
DOI: 10.1097/id.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Dental Implant Osseointegration Development in Low-Density Bone

Abstract: An osteotomic site overheating up to 60°C for 1 minute in low-density bone, before implant insertion, did not lead to implant failure, but it induced significant crestal bone loss during healing and lower %BIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Higher temperature values [17,18] of 60 • C for 1 min led to reduced BIC values around heated implants (mean 25.42% SD 1.49 in cancellous bone, mean 27.23% SD 12.44 in cortical bone) versus untreated implants (mean 38.05% SD 1.38 in cancellous bone, mean 31.94% SD 18.10 in cortical bone). However, only the implants inserted in the cancellous bone [17] presented significant differences.…”
Section: Bic Around Implants After Thermal Treatmentmentioning
confidence: 96%
See 3 more Smart Citations
“…Higher temperature values [17,18] of 60 • C for 1 min led to reduced BIC values around heated implants (mean 25.42% SD 1.49 in cancellous bone, mean 27.23% SD 12.44 in cortical bone) versus untreated implants (mean 38.05% SD 1.38 in cancellous bone, mean 31.94% SD 18.10 in cortical bone). However, only the implants inserted in the cancellous bone [17] presented significant differences.…”
Section: Bic Around Implants After Thermal Treatmentmentioning
confidence: 96%
“…Higher temperature values [17,18] of 60 • C for 1 min led to reduced BIC values around heated implants (mean 25.42% SD 1.49 in cancellous bone, mean 27.23% SD 12.44 in cortical bone) versus untreated implants (mean 38.05% SD 1.38 in cancellous bone, mean 31.94% SD 18.10 in cortical bone). However, only the implants inserted in the cancellous bone [17] presented significant differences. Similarly, at a lower temperature of 50 • C for 1 min, the cancellous bone led to a significantly lower BIC value, whereas around implants that were inserted in more cortical bone [18] no deviating BIC values were evaluated.…”
Section: Bic Around Implants After Thermal Treatmentmentioning
confidence: 96%
See 2 more Smart Citations
“…Several studies have shown that atraumatic surgical techniques that prevent the implant site overheating and primary stability are the two main factors involved in the success of osseointegration. 17 Bone perforation is a highly contested topic due to the heat production caused by this procedure. Several factors interfere with bone drilling and it is essential to develop new technologies in order to control them.…”
Section: Discussionmentioning
confidence: 99%